What to Say When There Is Nothing to Talk about - Mircea Dumitru; Frederick Kroon (Crítica)
In Reference without Referents, Mark Sainsbury aims to provide an account of reference that honours the common-sense view that sentences containing empty names like “Vulcan” and “Santa Claus” are entirely intelligible, and that many such sentences —“Vulcan doesn’t exist”, “Many children believe that Santa Claus will give them presents at Christmas”, etc.— are literally true. Sainsbury’s account endorses the Davidsonian program in the theory of meaning, and combines this with a commitment to Negative Free Logic, which holds that all simple sentences containing empty names are false. In this critical review, we pose a number of problems for this account. In particular, we question the ability of Negative Free Logic to make appropriate sense of the truth of familiar sentences containing empty names, including negative existential claims like “Vulcan doesn’t exist”.